(untitled) (Journal of Business and Management Research, 2017)
This study investigates the direct effect of components of celebrity endorsement (physical attractiveness, source creditability and celebrity brand matchup) on brand loyalty (attitudinal loyalty and behavioral loyalty). 220 general customers of branded products participated in the study. Multiple regression analyses were conducted to test hypotheses. Our result shows that physical attractiveness, source credibility expertise and celebrity brand match up has positive impact on developing attitude towards the brand. However, only physical attractiveness and celebrity brand matchup are associated with purchase intention. Practical and research implications of the findings are discussed and directions for future research are suggested.